Comparison of Asymmetry between Perceptual, Ocular, and Postural Vestibular Screening Tests - Timothy R. Macaulay; Scott J. Wood; Austin Bollinger; Michael C. Schubert; Mark Shelhamer; Michael O. Bishop; Millard F. Reschke; Gilles Clément (Brain Sciences, 2023)
Background: A better understanding of how vestibular asymmetry manifests across tests is important due to its potential implications for balance dysfunction, motion sickness susceptibility, and adaptation to new environments. Objective: We report the results of multiple tests for vestibular asymmetry in 32 healthy participants. Methods: Asymmetry was measured using perceptual reports during unilateral centrifugation, oculomotor responses during visual alignment tasks, vestibulo-ocular reflex gain during head impulse tests, and body rotation during stepping tests. Results: A significant correlation was observed between asymmetries of subjective visual vertical and verbal report during unilateral centrifugation. Another significant correlation was observed between the asymmetries of ocular alignment, vestibulo-ocular reflex gain, and body rotation. Conclusions: These data suggest that there are underlying vestibular asymmetries in healthy individuals that are consistent across various vestibular challenges. In addition, these findings have value in guiding test selection during experimental design for assessing vestibular asymmetry in healthy adults.